2008
DOI: 10.1111/j.1420-9101.2008.01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and quantitative genetic differentiation across Europe in yellow dung flies

Abstract: Relating geographic variation in quantitative traits to underlying population structure is crucial for understanding processes driving population differentiation, isolation and ultimately speciation. Our study represents a comprehensive population genetic survey of the yellow dung fly Scathophaga stercoraria, an important model organism for evolutionary and ecological studies, over a broad geographic scale across Europe (10 populations from the Swiss Alps to Iceland). We simultaneously assessed differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 115 publications
4
51
2
Order By: Relevance
“…Similar findings have been reported in other taxa (Demont et al 2008) and suggest genetic homogenisation over a large geographical scale and possibly high gene flow across the continent. Lack of information on the species' mating system and movements restricts our understanding of the mechanisms driving this gene flow.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings have been reported in other taxa (Demont et al 2008) and suggest genetic homogenisation over a large geographical scale and possibly high gene flow across the continent. Lack of information on the species' mating system and movements restricts our understanding of the mechanisms driving this gene flow.…”
Section: Discussionsupporting
confidence: 88%
“…Adults from K. Nera are known to emerge earlier than those from Dafni in local field conditions, and reciprocal transplant experiments (between these two populations in field) revealed a genetic basis to geographical variation of diapause intensity (Papanastasiou et al ., ), implying that the above populations are not ecologically exchangeable, despite the presence of gene flow (Rader et al ., ). Thus, the existence of local adaptation in the timing of diapause termination of R. cerasi pupae, even under conditions of ongoing gene flow, is in agreement with recent related studies regarding to the yellow dung fly and Drosophila montana (Demont et al ., ; Tyukmaeva et al ., ). Nevertheless, conditions experienced mostly by egg and larvae in the field before being brought back to the laboratory for collecting pupae remain uncontrolled (the initial rearing environment cannot be controlled in R. cerasi s because of lack of efficient rearing methodology; Köppler et al ., ) and might add some variability in diapause responses.…”
Section: Discussionmentioning
confidence: 99%
“…Given the small geographical distances among the islands of the Scilly archipelago, the discovery of population structure in an insect capable of flying short distances is remarkable, especially given that previous studies of other flying insects have found comparatively weaker population structure over much larger geographic scales (Demont et al , 2008). Our results also contrast somewhat with those of a previous study of M. jurtina that found relatively weak population structure across southern England, although in this particular case F st was estimated from allozymes that tend to have lower levels of variability than AFLPs (Goulson, 1993).…”
Section: Discussionmentioning
confidence: 99%